2008
DOI: 10.1186/1475-2891-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of low serum vitamin D3with anthropometry and markers of the metabolic syndrome and diabetes in overweight and obesity

Abstract: Low serum 25 hydroxyvitamin D3 (vitamin D3) is known to perturb cellular function in many tissues, including the endocrine pancreas, which are involved in obesity and type II diabetes mellitus (TIIDM). Vitamin D3 insufficiency has been linked to obesity, whether obesity is assessed by body mass index (BMI) or waist circumference (waist). Central obesity, using waist as the surrogate, is associated with the metabolic syndrome (MetSyn), insulin resistance, TIIDM and atherosclerotic cardiovascular disease (CVD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(131 citation statements)
references
References 37 publications
13
111
2
5
Order By: Relevance
“…30 kg/m 2 ) had a s25(OH)D , 75 nmol/l, compared with 68 % of the non-obese subjects. In another study on 243 ambulant adults (BMI 28 -50 kg/m 2 ) enrolled in a weight-loss study, s25(OH)D concentration was inversely associated with weight (P ¼ 0·0009), BMI (P¼0·005) and waist circumference (P¼0·03), but not body fat percentage (41) . This study also estimated a decrease of 0·74 nmol/l in s25(OH)D per 1 kg/m 2 increase in BMI.…”
Section: Obesitymentioning
confidence: 95%
See 1 more Smart Citation
“…30 kg/m 2 ) had a s25(OH)D , 75 nmol/l, compared with 68 % of the non-obese subjects. In another study on 243 ambulant adults (BMI 28 -50 kg/m 2 ) enrolled in a weight-loss study, s25(OH)D concentration was inversely associated with weight (P ¼ 0·0009), BMI (P¼0·005) and waist circumference (P¼0·03), but not body fat percentage (41) . This study also estimated a decrease of 0·74 nmol/l in s25(OH)D per 1 kg/m 2 increase in BMI.…”
Section: Obesitymentioning
confidence: 95%
“…Another recent cross-sectional analysis of 1654 men and women reported a substantially lower OR for the MetS in the highest quintile of s25(OH)D (median 88·0 nmol/l; OR 0·15) compared with the lowest quintile (median 26·8 nmol/l; OR 0·46) (39) (40 -42) . McGill et al (41) showed in 243 obese adults, 80 % of whom were women (age 47·6 (SD 12) years), that while s25(OH)D concentration was inversely associated with waist circumference, BMI and HbA 1c , there was no association with the MetS. Using data from the Rancho Bernardo Study (n 1070; aged 44-96 years), Reis et al (42) showed no association between s25(OH)D and MetS risk despite the strong positive association between PTH and MetS risk (OR 2·02; 95 % CI 0·96, 4·24).…”
Section: Cardiometabolic Syndromementioning
confidence: 99%
“…Evidence that supports a link between vitamin D status and an increase in energy expended from a meal (26) provides an explanation of the role of vitamin D to reduce adiposity. In the study of 250 overweight and obese adults of different ethnicities, serum 25(OH)D was shown to be inversely related to weight (r 2 0·21), BMI (r 2 0·18) and waist circumference (r 2 0·14), but not fat mass (27) . These results suggest that the relationship of vitamin D status was specific to waist circumference, an independent risk factor for disease, and not to fat mass.…”
Section: Body Composition Vitamin D and Diabetesmentioning
confidence: 99%
“…Vitamin D has anti-inflammatory effects and has a modulation role in the immune system. The effect of the immune modulating effects of vitamin D applies from its receptors on the majority immune cells (14). Vitamin D reduces the activity of nuclease factor, interleukin and IFN γ, which results in lowering of the inflammation process (15).…”
Section: Discussionmentioning
confidence: 99%